2017
DOI: 10.1093/fampra/cmx007
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of optimised clinical medication reviews for geriatric patients: Opti-Med a cluster randomised controlled trial

Abstract: The study intervention did not influence QoL and geriatric problems. The higher percentage of solved DRPs in the intervention group did not result in effects on the patient's health. CMRs on a large scale seem not meaningful and should be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 26 publications
(27 reference statements)
3
30
0
1
Order By: Relevance
“…Although previous research in different settings of care assumes a positive effect of an SMR on health outcomes such as QoL and cost-effectiveness, contradictory results are found. Willeboordse et al (2017) found no effect of a medication review concerning QoL in 518 geriatric patients and the chronic use of ≥1 prescribed drug [ 59 ]. One explanation might be the non-complexity of the selected patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous research in different settings of care assumes a positive effect of an SMR on health outcomes such as QoL and cost-effectiveness, contradictory results are found. Willeboordse et al (2017) found no effect of a medication review concerning QoL in 518 geriatric patients and the chronic use of ≥1 prescribed drug [ 59 ]. One explanation might be the non-complexity of the selected patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Voor een medicatiebeoordeling zijn verschillende werkwijzen beschikbaar (zie o. a. www.medicijngebruik.nl), al of niet in FTO-verband. Er zijn goede ervaringen met de inzet van een expertteam, bestaande uit een (huis)arts en een apotheker voor de farmacotherapeutische analyse en het opstellen van het farmacotherapeutisch behandelplan [12].…”
Section: [Figuur 2] Multidisciplinaire Richtlijn 'Polyfarmacie Bij Ouunclassified
“…13 Studies have revealed that the use of STRIP Assistant by general practitioners and pharmacists increases appropriate medication decisions (58-76%), decreases inappropriate decisions (42-24%) and increases the percentage of solved drug-related problems in test cases from general practice. 14,15 As little is known about the effect of STRIP Assistantgenerated prescribing recommendations in a hospital setting, we evaluated whether prescribing recommendations made with the use of the STRIP Assistant improved prescribing in a preoperative geriatric outpatient population. The primary outcome was the number of resident-implemented medication changes made because of PIMs, PPOs, and suboptimal dosages; a secondary outcome was 3-month postoperative mortality.…”
Section: Introductionmentioning
confidence: 99%